Colonization of guinea grass by anaerobic rumen fungi in swamp buffalo and cattle - Ho, Y.W.; Abdullah, N.; Jalaludin, S. (Elsevier, 1988)
No apparent differences in the invasion and colonization of guinea grass by anaerobic rumen fungi could be distinguished between swamp buffalo and cattle. In both animals, zoospores had attached to leaf and stem fragments 15 min after rumen incubation. At 30 min, rhizoids of germinated zoospores were present in many thin-walled cells and many of the rhizoids were observed to produce “appressoria” for penetration of cell walls about 1 h after incubation. By 6 h, sclerenchyma and vascular tissues were extensively colonized and disruption and degradation of tissues occurred in areas with profuse colonization of rhizoids. Most thin-walled cells were degraded after 24 h of incubation and large sporangia were attached to the vascular cylinders. Sporangia were predominantly spherical, ovoid or oval in shape and sporangia which were cylindrical, filiform or fusiform with an elongated pointed tip were of lesser occurrence. At 48 h, many empty uniporous or multiporous sporangia, which probably were remains of sporangia after the liberation of zoospores, were observed. Some spores with thick, warty walls were also observed at 48 h in buffalo. These warty spores resemble resting spores of some aquatic chytrids and may play a part in the dispersal of the rumen fungi from animal to animal.